Mac OS X Panther for Unix geeks - Jepson, Brian, 1967- (O'Reilly, 2004)
With its rep for being the sort of machine that won't intimidate even the most inexperienced users, what's the appeal of the Mac® for hard-core geeks? The Mac has always been an efficient tool, pleasant to use and customize, and eminently hackable. But now with Mac OS® X's BSD core, many a Unix® developer has found it irresistible. The latest version of Mac OS X, called Panther, makes it even easier for users to delve into the underlying Unix operating system. In fact, you can port Linux® and Unix applications and run them side-by-side with your native Aqua® apps right on the Mac desktop. Still, even experienced Unix users may find themselves in surprisingly unfamiliar territory as they set out to explore Mac OS X. Even if you know Macs through and through, Mac OS X Panther is unlike earlier Macs, and it's radically different from the Unix you've used before. Enter Mac OS X Panther for Unix Geeks by Brian Jepson and Ernest E. Rothman, two Unix geeks who found themselves in the same place you are. The new edition of this book is your guide to figuring out the BSD Unix system and Panther-specific components that you may find challenging. This concise book will ease you into the Unix innards of Mac OS X Panther, covering such topics as: A quick overview of the Terminal application, including Terminal alternatives like iTerm and GLterm Understanding Open Directory (LDAP) and NetInfo Issues related to using the GNU C Compiler (GCC) Library linking and porting Unix software An overview of Mac OS X Panther's filesystem and startup processes Creating and installing packages using Fink and Darwin Ports Building the Darwin kernel Using the Apple® X11 distribution for running X Windows® applications on top of Mac OS X The book wraps up with a quick manpage-style reference to the "Missing Manual Pages"--Commands that come with Mac OS X Panther, although there are no manpages. If you find yourself disoriented by the new Mac environment, Mac OS X Panther for Unix Geeks will get you acclimated quickly to the foreign new areas of a familiar Unix landscape